2013
DOI: 10.1186/2045-8118-10-2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the blood–brain barrier using stem cell sources

Abstract: The blood–brain barrier (BBB) is a selective endothelial interface that controls trafficking between the bloodstream and brain interstitial space. During development, the BBB arises as a result of complex multicellular interactions between immature endothelial cells and neural progenitors, neurons, radial glia, and pericytes. As the brain develops, astrocytes and pericytes further contribute to BBB induction and maintenance of the BBB phenotype. Because BBB development, maintenance, and disease states are diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 139 publications
(163 reference statements)
3
102
0
Order By: Relevance
“…A promising new development from the Shusta group is an in vitro BBB model derived from human pluripotent stem cells (hPSCs), involving initial codifferentiation of endothelial and neural cells, then purifi cation and further maturation of the endothelial cells to develop a full BBB-like phenotype (Lippmann et al 2012(Lippmann et al , 2013 ). It will be interesting to see how well this model replicates the in vivo behaviour in further characterization studies and applications, and whether it proves suitable for screening BBB permeation of a range of drug chemistries, including those subject to transfer by carrier-mediated mechanisms, and nanocarriers and engineered peptides and proteins, candidates for RMT.…”
Section: Human Pluripotent Stem Cellsmentioning
confidence: 99%
“…A promising new development from the Shusta group is an in vitro BBB model derived from human pluripotent stem cells (hPSCs), involving initial codifferentiation of endothelial and neural cells, then purifi cation and further maturation of the endothelial cells to develop a full BBB-like phenotype (Lippmann et al 2012(Lippmann et al , 2013 ). It will be interesting to see how well this model replicates the in vivo behaviour in further characterization studies and applications, and whether it proves suitable for screening BBB permeation of a range of drug chemistries, including those subject to transfer by carrier-mediated mechanisms, and nanocarriers and engineered peptides and proteins, candidates for RMT.…”
Section: Human Pluripotent Stem Cellsmentioning
confidence: 99%
“…This result suggests that alterations in junctional barrier properties can modify the route of leukocyte transmigration. As further confirmation for the role of 'junctional tightness' itself in the above results, we took advantage of an established agent-independent means of progressively reducing primary rat brain MVEC barrier strength through extended culture passaging (Lippmann et al, 2013). We found that by culturing rat brain MVECs for .4 passages, we could promote a substantial decrease in electrical resistance to ,26 Vcm 2 , which was coupled with a shift towards a majority of diapedesis occurring by the paracellular route (Fig.…”
Section: Introductionmentioning
confidence: 95%
“…However, to be an effective screening assay an in vitro BBB model needs to be robust, reproducible, and with highly restrictive tight junctions to mimic the in vivo condition. A number of in vitro BBB models have been developed, including several recently reported (Bernas et al, 2010;Sano et al, 2010;Hatherell et al, 2011;Lippmann et al, 2013;Xue et al, 2013), but most of the cell line models and many of the primary cultures show low transendothelial electrical resistance (TEER), indicating a leaky cell monolayer. A few models do show high TEER and are in principle suitable for permeability assays (Franke et al, 1999 (Culot et al, 2008;Vandenhaute et al, 2012).…”
Section: Introductionmentioning
confidence: 99%